Globalization, regulatory arbitrage and efficient oversight - Guichard, Eric-V. (UWI St. AugustineTT, 2009)
Looks at whether a multilateral approach to regulatory oversight, as suggested by the G20, effectively eliminate arbitrage as we know it.